Perbedaan Resistensi Siswa Laki-laki dengan Siswa Perempuan di SMP Telekomunikasi Pekanbaru - Priadi, Galgian; Umari, Tri; Donal, Donal; Mansor, Rosnidar (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2023)
This study aimed to investigate the differences in resistance levels exhibited by male and female students towards their teachers. The research employed a quantitative approach with a comparative design, involving 75 students from a Junior High School named SMP Telekomunikasi Pekanbaru. The resistance levels of the students were measured using a resistance scale composed of various indicators. The validity and reliability of the research instrument were established through validity and reliability tests. The obtained data were subjected to Independent T-Test analysis to determine if there were significant differences in resistance between male and female students. The results indicated that both male and female students exhibited moderate levels of resistance towards their teachers. However, the analysis of the Independent T-Test revealed that there was no significant difference in resistance levels between the two genders (p > 0.05). These findings suggest that gender did not play a significant role in influencing the resistance behaviors displayed by the students. In conclusion, the study contributes to the understanding of student resistance towards teachers, indicating that both male and female students exhibit moderate levels of resistance. The absence of significant gender-based differences in resistance levels suggests that other factors, such as teaching methodologies, classroom dynamics, and student perceptions, might be more influential in shaping resistance behaviors. These results highlight the importance of fostering positive teacher-student interactions and creating an environment where students feel heard and understood, regardless of their gender.